E-Learning Telah Menjadi Platform Pembelajaran Yang Dominan di Era Society 5.0 - Shohwatul Hana; Aji Wibawa (Universitas Ngeri Malang, 2022)
The fourth industrial revolution is a technological advancement that centers around machine-based systems as a solution to human error, with the aim of improving life on a global scale. While Japan considers society 5.0 as a substitute for technology-driven fourth industrial revolution remains a crucial component in supporting global education, particularly through the implementation of an e-learning system. This study employs a qualitative approach and presents descriptive research, concluding that e-learning is a safe and viable option in the ongoing industrial revolution 4.0. By means of electronic learning, students are able to easily engage in the learning process, while educators such as lecturers and teachers can prepare learning materials and upload them onto the e-learning platform. Such examples of e-learning can effectively enhance the practicality of teaching and learning activities, with students able to produce interactive activities and easily access teaching materials uploaded onto the platform. Perkembangan adalah hal yang terjadi dalam Jepang menganggap pendekatan